A search for the final maritime boundary delimitation for Timor-Leste - Silva, Adelsia Maria Assunção Coelho da (2020)
Maritime boundary delimitation is one of the oldest disputes between coastal States that remain until present and it is very likely continue to take place in the future. The main international legal framework on this subject matter is the United Nations Convention on the Law of the Sea regulates how States that is supported by the practice of international courts and tribunal. Until today over 200 maritime boundary disputes remain unresolved. There are many factors contributed to such, one of the factors is the difference view on how it should be delimited that is further complicated by the non-possibility to submit the dispute to international adjudication. This is due the fact that despite UNCLOS provides that all of maritime boundary delimitation shall be resolved by the parties and if cannot shall be submitted to one dispute settlement entailing binding decision in accordance with international law in order to achieve an equitable solution, the Convention also provides the possibility of States excluding themselves from such mechanism by making declaration under Article 298 (1) of UNCOS. One of Timor-Leste’s neighbours, Australia, made that declaration. Following the failure to solve their maritime boundary delimitation in the Timor Se for over 15 years, Timor-Leste submitted the dispute to compulsory conciliation under UNCLOS. This was the last evenue for Timor-Leste to finalise its maritime boundary delimitation. This research will try to analyse maritime boundary delimitation between Timor-Leste and Australia in accordance with International law that will be tried to established by looking at the rule of delimitation in the Convention and the practices developed by international courts and Tribunals. Following of that, as the dispute of the parties managed to be solved by compulsory conciliation, this thesis will then scrutinise the maritime boundary delimitation agreed by the parties.